Inverse Approach to the Forming Simulation of Tailored Heat Treated Blanks - Staud, Detlev; Merklein, Marion (International Journal of Material Forming, 2008)
While climate protection and environmental conservation gain an increasingly significant role, the weight reduction of car body parts is a consequence of the need for efficient fuel consumption and for reduced CO2-emissions. Therefore advanced material and production methods have to be developed to meet this requirement. Since steel sheet metal parts cannot be substituted directly with lightweight aluminium parts, due to its minor formability, so called Tailored Heat Treated Blanks (THTB) are presented in this work. THTB are locally heat treated aluminium blanks from the 6000-series alloy, leading to a significantly improved formability for the manufacturing of complex aluminium car body parts. The enhancement of formability is reached by a local laser heat treatment before the forming operation. Since there is a strong influence of the heating on the forming process, a finite-element simulation of the process sequence is a prerequisite for the cost-effective usage of the THTB. The presented inverse approach considers first the desired forming result and enables the precise determination of heat treatment areas including the specific heat treatment temperatures. In conclusion the numerical solved appropriate strength pattern is verified with experimental test results of THTB. © Springer/ESAFORM 2008.
LFT Import::2019-07-29 (1558)
Keywords: Aluminium; Finite element simulation; Parameter identification